Konsekuensi Hukum dan Upaya Hukum Mengenai Wanprestasi dalam Kontrak - Karaniya, Avishtya Siti; Lidowati, Alvina Maretia; Zevanya, Cristella; Tarigan, Fortius Leonard Gersang; S, Surahmad (Media Hukum Indonesia (MHI), 2024)
Breach of contract can arise from various factors, such as financial inability, miscommunication, or even deliberate action. In the context of a sale and purchase agreement, breach of contract can arise from various causes, such as late delivery of goods, non-conformity of the quality of goods, or even the inability to pay the agreed price. The legal impact of a breach of contract on a sale and purchase agreement is very significant. The party who suffers a loss due to breach of contract has the right to claim compensation, cancel the contract, or file other claims in accordance with applicable law. In overcoming breach of contract, the injured party can take several steps, such as sending a warning letter or filing a lawsuit. However, in overcoming breach of contract, it is necessary to be careful and maintain sufficient evidence to prove that the party committing the breach of contract has failed to fulfill the obligations agreed in the contract. The normative legal research method uses a literature study approach which is carried out by examining the approach of theories, concepts, reviewing laws and regulations related to this research or the approach of legislation. The results of the study show that when one party to an agreement fails to fulfill its end of the bargain, a breach of contract occurs. There are many different causes, such as carelessness, malice, economic shifts, broken promises, unforeseen circumstances, or misinterpretation of the terms of the contract. Starting with an initial warning, lawsuit, deliberation, and sometimes an appeal or cassation, the legal process for filing a breach of contract case consists of a series of stages.